2016
DOI: 10.1002/hed.24364
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to guideline‐recommended process measures for squamous cell carcinoma of the head and neck in Ontario: Impact of surgeon and hospital volume

Abstract: Adherence rates to guideline-recommended processes of care in the surgical management of patients with head and neck cancer in Ontario were moderate and should be improved. Although adherence rates seem proportional to surgical volume, even the highest volume centers have room to improve. © 2016 Wiley Periodicals, Inc. Head Neck 38: E1987-E1992, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 23 publications
(32 reference statements)
3
40
0
Order By: Relevance
“…A recently published study using population-based data in Ontario demonstrates similar results with less than perfect compliance with key guideline recommended processes of care: pre-operative imaging (82.5 %), pre-operative head and neck imaging (71.8 %), pre-operative multidisciplinary care (57.6 %), and post-operative follow up visits (76.7 %) [26]. Nearly all of these measures were higher among higher volume surgeons and hospitals.…”
Section: Beyond the Volume-outcome Relationshipsupporting
confidence: 74%
“…A recently published study using population-based data in Ontario demonstrates similar results with less than perfect compliance with key guideline recommended processes of care: pre-operative imaging (82.5 %), pre-operative head and neck imaging (71.8 %), pre-operative multidisciplinary care (57.6 %), and post-operative follow up visits (76.7 %) [26]. Nearly all of these measures were higher among higher volume surgeons and hospitals.…”
Section: Beyond the Volume-outcome Relationshipsupporting
confidence: 74%
“…In this study, a 50% relative decrease in overall survival was found for patients who initiate adjuvant therapy more than 6 weeks after surgery, a 15% relative increased risk of death persisted on multivariable analysis adjusting for numerous confounding factors, and a 20% relative increased risk of death in the propensity-matched subset analysis. These findings led further support to the idea that, at least with regards to the timing of adjuvant therapy, guideline-adherent head and neck oncology care is quality care 3941 .…”
Section: Discussionmentioning
confidence: 70%
“…Discrepancies between guideline-directed care and delivered care have been described across the spectrum of pretreatment evaluation, treatment, and posttreatment surveillance for patients with oral cavity cancer 13 and laryngeal cancer 14,15 and in the receipt of adjuvant therapy for patients who have head and neck cancer with high-risk features. 18 Continued effort will be required to improve the quality of care delivered to these patients. 18 Continued effort will be required to improve the quality of care delivered to these patients.…”
Section: Frequency Of Care That Does Not Adhere To Nccn Guidelinesmentioning
confidence: 99%